Zrzeszanie się producentów rolnych jako sposób poprawy pozycji konkurencyjnej gospodarstw rolnych - na przykładzie grupy producentów owoców i warzyw "Hortus" - Bartkiewicz, Halina (Uniting the Agricultural Producers as the Way to Improve the Farms' Competitive Situation - the Example of "Hortus" - Fruit and Vegetables Producers' Group, 2006)
The splitting up among the agricultural producers causes the difficulties in coping with customers' needs and expectations. Combining the market offer of many farms eliminates the competition among them and increases their economic potential, strengthens the competitive position towards others. The article presents the activity of the fruit and vegetables producers' group called "Hortus" in lubuskie voivodeship. The work shows the reasons and profits of taking up the common action (especially the competitive aspects) in opinion of the "Hortus" group's leaders and its members.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 57-62